2021
DOI: 10.3389/fpubh.2021.646663
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Syphilis in People Living With HIV/AIDS in the State of Pará, Northern Brazil

Abstract: Syphilis continues to be a public health problem worldwide and its incidence has increased in people living with HIV/AIDS in recent years. This study determined the prevalence and factors associated with syphilis in people living with HIV/AIDS in the city of Belém, northern Brazil. A cross-sectional study was conducted from June to November 2018. A total of 500 people living with HIV/AIDS attended at a specialized unit of the public health network of the State of Pará were studied. Questionnaires were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
(20 reference statements)
1
13
0
4
Order By: Relevance
“…Syphilis and HIV co-infection is viewed as a potentially dangerous combination since both diseases negatively impact treatment response to each other. Previous studies observed serological non-response to syphilis treatment, cognitive impairment, and virological failure of ART among syphilis and HIV co-infected patients ( 21 23 ). Our study observed that nearly one-fourth of the study population had co-infection with HIV.…”
Section: Discussionmentioning
confidence: 93%
“…Syphilis and HIV co-infection is viewed as a potentially dangerous combination since both diseases negatively impact treatment response to each other. Previous studies observed serological non-response to syphilis treatment, cognitive impairment, and virological failure of ART among syphilis and HIV co-infected patients ( 21 23 ). Our study observed that nearly one-fourth of the study population had co-infection with HIV.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of HIV was 15.26% (38/249); syphilis was 27.71% (69/249); and HIV/syphilis co-infection was 9.24% (23/249) in aged > 50 years [24]. Among people living with HIV, the prevalence of syphilis (co-infection) was 2.1% (11/511) among those with aged over 50 years in the African [23] and 3.7% (10/270) in people aged over 40 years with HIV in Belem, Brazilian Amazon [30]. In Zimbabwe, among 222 cases of syphilis, 45% (100) were with HIV, the only factor associated with syphilis in both females and males at p < 0.001 [26].…”
Section: Discussionmentioning
confidence: 98%
“…The syphilis infection almost triples the risk of HIV acquisition [8]. Several studies have been conducted with people living with HIV, increasing the prevalence of syphilis [8,24,30]. In England, a trend over age and time showed that rates of STI were increasing in the older age groups, including those aged 45-64 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations